Evaluasi Kinerja Pegawai Berdasarkan Hasil Nilai Indeks Kepuasan Masyarakat Pada Pelayanan Kantor Imigrasi Kelas I Non Tpi Karawang Periode Mei 2023 - Dwi Rahmadia Putri; Puji Isyanto; Dini Yani (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the level of public satisfaction with public services Immigration Office Class I Non TPI Karawang. This research is a type of descriptive research. This research was conducted at the Non-TPI Karawang Class I Immigration Office in May 2023. The data collection technique was carried out by filling out a QR Code-based questionnaire in collaboration with the Legal and Human Rights Research and Development Agency. And from the results of this study it can be seen that the Community Satisfaction Index (IKM) for Class I Non-TPI Karawang Immigration Office services received a Very good predicate.